Prophylactic catheter ablation of ventricular tachycardia before cardioverter‐defibrillator implantation in patients with non‐ischemic cardiomyopathy: Clinical outcomes after a single endocardial ablation. Issue 3 (4th February 2015) - Suzuki, Atsushi; Yoshida, Akihiro; Takei, Asumi; Fukuzawa, Koji; Kiuchi, Kunihiko; Takami, Kaoru; Itoh, Mitsuaki; Imamura, Kimitake; Fujiwara, Ryudo; Nakanishi, Tomoyuki; Yamashita, Soichiro; Matsumoto, Akinori; et al.
Abstract: Background: Outcomes related to prophylactic catheter ablation (PCA) for ventricular tachycardia (VT) before implantable cardioverter‐defibrillator (ICD) implantation in non‐ischemic cardiomyopathy (NICM) are not well characterized. We assessed the efficacy of single endocardial PCA in NICM patients. Methods: We retrospectively analyzed 101 consecutive NICM patients with sustained VT. We compared clinical outcomes of patients who underwent PCA (ABL group) with those who did not (No ABL group). Successful PCA was defined as no inducible clinical VT. We also compared the clinical outcomes of patients with successful PCA (PCA success group) with those of the No ABL group. Endpoints were appropriate ICD therapy (shock and anti‐tachycardia pacing) and the occurrence of electrical storm (ES). Results: PCA was performed in 42 patients, and it succeeded in 20. The time to ES occurrence was significantly longer in the ABL group than in the No ABL group ( p =0.04). The time to first appropriate ICD therapy and ES occurrence were significantly longer in the PCA success group than in the No ABL group ( p =0.02 and p <0.01, respectively). Conclusion: Single endocardial PCA can decrease ES occurrence in NICM patients. However, high rates of VT recurrence and low success rates are issues to be resolved; therefore, the efficacy of single endocardial PCA is currently limited.